Output gap determinants in Ethiopia - Adisu Abebaw Degu (Cogent Economics & Finance, 2021)
The output gap measured as the percentage deviation of actual output from its potential level is an indicator of an economy's achievement. Output gap has been an important concept used for forming of policies. In this study, we estimated the potential output and output gap, established some of its macro-economic determinants for the Ethiopian economy. By using yearly data spanning from 1990 to 2018, the study estimated the potential output and output gap using HP filtering, and production function approaches. Accordingly, both approaches indicated that the output gap has been fluctuating over the study period-indicating the actual output inconsistently and frequently deviating from its potential level. Mainly, in 1996 and 2003, the actual output showed the highest positive and negative deviations from its potential, respectively. The study also examined the effect of some macro-economic indicators on the output gap using the ARDL framework. Accordingly, inflation, trade openness, lending rate, and FDI are found to be having a significant effect on the output gap. Lending rate and trade openness have positive and significant effect, whereas inflation and FDI have a negative significant effect on the output gap. This study suggests; augmenting domestic production and utilization capacity, avoiding unrestricted importation and, export diversification, lowering lending rate and increasing FDI inflow; helps to reduce output gap. Besides, understanding the trend of potential and output gap would be helpful in dealing with inflation.
Keywords: C32; E10; E32; O4; 330; ARDL; HP filer; output gap; Potential output